Nonalam Disaster Management Policy for The Spread of Covid-19 in The Framework of Regional Autonomy (Central Java Provincial Government Case Study) - Muhammad Nurul Huda; Titin Purwaningsih; Hammam (Universitas Muhammadiyah Sidoarjo, 2021)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by a type of coronavirus, this virus was first detected in Wuhan, China. Seeing the spread, the transmission of Covid-19 has increased very quickly across countries and continents. The Central Government has declared the non-natural disaster status of the spread of Covid-19 as a National disaster. Seeing the impact of the Covid-19 Pandemic not only causing a health emergency but also having an impact on the social, economic, political, cultural, educational and other fields so that its response requires synergy between the Central Government, Regional Government, the private sector, and the community. This study aims to analyze the effectiveness of non-natural disaster management policies for the spread of Covid-19 by the Central Government and Central Java Provincial Government within the framework of the division of authority through the regional autonomy law. This research method uses descriptive qualitative, using a statute approach and a case approach. The results show that the distribution of authority to the Regional Government to regulate their own household affairs has a positive impact on accelerating the management of non-natural disasters from the spread of Covid-19, on the other hand the negative impact is the potential for overlapping between central and regional policies. However, the potential for overlapping policies can be minimized as long as the Central Government is able to absorb the aspirations of the Regional Government and the Regional Government pays attention to the policies of the Central Government.